Breaking with old ideas: Chinese students' perceptions of China's 'neoliberal turn' in higher education. Issue 3 (4th May 2019) - Gong, Qian; Dobinson, Toni
ABSTRACT: Maoist policy in China emphasised the peasants and workers. It integrated academic study with productive labour to nurture socialist citizens useful for the nation's modernisation. More recently, China has been described as having a 'neoliberal turn' but many see the situation as more complex than this due to the significant role given to the state in economic development and governance. Using the film 'Breaking with Old Ideas' [Li, W. (1975). Breaking with old ideas [Motion picture]. China: Beijing Film Studio] to inform, and stimulate participants, this study examined how a group of 15 Chinese students at an Australian university perceived the transformation of higher education in China. Findings generated from written responses and interviews addressed the relationship between neoliberal imaginings and Foucauldian subjectification processes in post-Maoist China, supporting the thesis that China cannot be called neoliberal in the traditional sense of the word. In terms of education, there co-exist socialist and neoliberal rhetorics with tensions between Confucianism, suzhi (quality) and traditional examination-driven models.